Treatment Trends in Paediatric Dentistry with Evolving Training and Education of Postgraduate Students in India: A Retrospective Study - Khadeeja Kulood Mazhuvanchery; Rishi Tyagi; Namita Kalra; Amit Khatri (Association of Support to Oral Health Research (APESB), 2024)
Objective: To assess and analyse the pattern of dental treatment services and their characteristics provided to children by evaluating the clinical use of materials and prevalence in material research in a major postgraduate paediatric tertiary care hospital in India over three years. Material and Methods: Institutionally approved retrospective analysis was conducted by auditing the clinical records of 2644 patients who visited and had treatment in the Outpatient and Inpatient Department of Paedodontics and Preventive Dentistry from January 2017 to December 2019. Clinical logbooks of postgraduate students were analysed by crosschecking with the department's data warehouse. Results: Out of the 2644 children who had treatment, more than two-thirds of them were in the age group of 4-7 years old. Around 5.6% of the patients were specially-abled children. Extraction (33.5%) was the most common treatment, followed by restorative treatment (29.1%). Endodontic treatment had a prevalence of 19.8%, with a reduced prevalence of preventive treatment care (0.5%). Patients who had traumatic tooth management included 2.8% of the study population. The prevalence of preventive care was found to be 2.1%. The teaching curriculum with theoretical and clinical skill practices was under the country's assigned authority. Conclusion: Despite advancements in paediatric dentistry, more children had extraction treatment with less observed utilization of preventive care. The widening of the training prospectus includes comprehensive care and an amplified focus on preventive care in the academic curriculum of paediatric postgraduates, which is the need of the hour.